Pengaruh Job Description, Job Specification Dan Leadership Terhadap Kinerja Organisasi Pada Forum Lembaga Legislatif Mahasiswa Indonesia Koordinator Malang Raya - Fakhrizal Akbar; Hadi Sunaryo; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This research was conducted at the Indonesian Students Legislative Board coordinator of Malang Raya (FL2MI Korda Malang Raya). The purpose of this research is to test and analyze the influence of Job Description, Job Specification and Leadership towards organizational performance.The variables used are Job Description, Job Specification and Leadership as independent variables, while organizational performance variables are dependent variables. The samples used in this study were 74 members of the FL2MI Korda Malang Raya Using a method of calculation of the formula Slovin. Data collection method by collecting primary data. The analyses used include instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing and using multiple regression analysis of SPSS 25.0 for Windows software.The results showed that the Job Description variable had a significant effect on the organization's performance FL2MI Korda Malang Raya, the Job Specification variable has no significant effect on the organization performance FL2MI Korda Malang Raya, while the Leadership variable has a significant effect on the organizational performance FL2MI Korda Malang Raya.Keywords:Job description,Job Specification,leadership and organizational performance,